2010
DOI: 10.1017/s107407080000331x
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Grazing Termination Date for Dual-Purpose Winter Wheat Production

Abstract: Dual-purpose winter wheat (fall-winter forage plus grain) production is an important economic enterprise in the southern Great Plains. Grazing termination to enable grain production is a critical decision. The objective is to determine the optimal grazing termination date for dual-purpose wheat. The value of knowing the occurrence of first hollow stem (FHS), a wheat growth threshold for grazing termination, is also determined. Results indicate that for most price situations grazing should be terminated at or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Similarly, by assumption, the very unfavorable conditions of 1992 could be expected to occur only once in six years. As could be expected, the Taylor et al (2010) results fall roughly half way between those of Fieser et al and Redmon et al (1996). Taylor et al (2010) found an expected 3% reduction in grain yield for grazing one day past FHS, an 8% reduction at three days past FHS, and an 18% reduction at seven days past FHS.…”
Section: Wheat Yields and Extended Grazingsupporting
confidence: 61%
See 2 more Smart Citations
“…Similarly, by assumption, the very unfavorable conditions of 1992 could be expected to occur only once in six years. As could be expected, the Taylor et al (2010) results fall roughly half way between those of Fieser et al and Redmon et al (1996). Taylor et al (2010) found an expected 3% reduction in grain yield for grazing one day past FHS, an 8% reduction at three days past FHS, and an 18% reduction at seven days past FHS.…”
Section: Wheat Yields and Extended Grazingsupporting
confidence: 61%
“…Addressing the contradictory findings from these two studies, Taylor et al (2010) revisited the grazing termination date issue. They combined data from the two studies, used a more precise statistical modeling approach, and assumed that conditions reflected in each of the six years were equally likely to occur.…”
Section: Wheat Yields and Extended Grazingmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tembo et al () random plateau model allows year‐to‐year variation of the yield responsiveness to nitrogen fertilizer. This model has been extensively used in the literature and some examples are Biermacher et al (), Taylor et al (), Brorsen and Richter (), Boyer et al (), Falconer et al (), and Harmon et al (). The plateau random effect allows an upward or downward shift of the average yield potential depending on the environmental condition.…”
Section: Empirical Models and Estimationmentioning
confidence: 99%
“…If unfavorable conditions exist for grain development or beef production is priority, grazing will extend into late spring, which is typically termed as graze out systems. Taylor et al (2010) estimated that 50%, or 2.43 million ha (6 million ac), of planted wheat in New Mexico, Oklahoma, and Texas are managed to produce dual-purpose wheat.…”
mentioning
confidence: 99%